CKD is associated with recurrent ischemia but not with hemorrhagic transformation in acute ischemic stroke patients. (March 2014) - Micozkadioglu, Hasan; Ozelsancak, Ruya; Giray, Semih; Arlier, Zulfikar
Abstract Background: We investigated the associations of Recurrent Ischemic Stroke (RIS) and Hemorrhagic Transformation (HT) with CKD in acute ischemic stroke patients. Method: The subjects were 160 patients, divided into two groups: with eGFR <60 mL/min/1.73 m2 (CKD), with eGFR ≥60 mL/min/1.73 m2 (without CKD). Results: Subjects having DM (p = 0.018), CKD (p = 0.025) and treated with ACEI/ARB (p = 0.039) revealed association with RIS. Regression analysis disclosed only CKD (p = 0.04). Carotid artery stenosis (p = 0.030) and serum calcium levels (p = 0.013) showed significant association with HT. Conclusion: Our results disclosed that CKD could be a risk factor for RIS. There is no relation between CKD and HT.